2013
DOI: 10.5324/fn.v33i0.1579
|View full text |Cite
|
Sign up to set email alerts
|

Arctic charr (Salvelinus alpinus) squeezed in a complex fish community dominated by perch (Perca fluviatilis)

Abstract: Sandlund OT, Haugerud E, Rognerud S and Borgstrøm R. 2013. Arctic charr (Salvelinus alpinus) squeezed in a complex fish community dominated by perch (Perca fluviatilis). Fauna norvegica 33: 1-11.In the complex fish community of Lake Skasen, southeastern Norway, the relative population density, habitat use and diet of Arctic charr, perch, roach and burbot was studied by a gill net survey during June-September 2010. A marked segregation in habitat use was observed, with Arctic charr and burbot captured in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Consequently, all three species investigated in this study feed on a mixture of pelagic and profundal diet, also confirmed by the stomach analyses. A. charr appeared to consume most profundal prey, as it was previously found to be the weaker competitor against whitefish [58,59], thus forced to occupy the less energetically favourable profundal niche [60][61][62]. This was also reflected in the highest δ 15 N ratios measured for A. charr (Table 1), as profundal primary consumers produce higher baseline δ 15 N than pelagic zooplankton [39].…”
Section: Age Size and Weight Distributions Stable Isotope Ratios Ansupporting
confidence: 54%
See 1 more Smart Citation
“…Consequently, all three species investigated in this study feed on a mixture of pelagic and profundal diet, also confirmed by the stomach analyses. A. charr appeared to consume most profundal prey, as it was previously found to be the weaker competitor against whitefish [58,59], thus forced to occupy the less energetically favourable profundal niche [60][61][62]. This was also reflected in the highest δ 15 N ratios measured for A. charr (Table 1), as profundal primary consumers produce higher baseline δ 15 N than pelagic zooplankton [39].…”
Section: Age Size and Weight Distributions Stable Isotope Ratios Ansupporting
confidence: 54%
“…A. charr was caught all year, with the highest presence in autumn, as they are likely forced to occupy the profundal niche by competition with whitefish [58,59,61,62]. E. smelt was also caught in the profundal zone all year, but fewer individuals were caught in summer.…”
Section: Use Of the Profundal Habitatmentioning
confidence: 99%
“…Typical effects of eutrophication are increased primary productivity with decreased dissolved oxygen (Smith & Schindler, ; Vonlanthen et al ., ). Therefore, it is expected that eutrophication and species introductions currently pose a greater threat to southern S. alpinus populations than predicted increases in temperature, as S. alpinus typically occur in deep lakes that provide a thermal refuge from negative interspecific interactions (Jensen et al ., ; Sandlund et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Sandlund, Haugerud, Rognerud and Borgstrøm () showed that there was a marked segregation in habitat use, with Arctic char observed in the profundal and deep areas of the pelagic zone, and perch and roach captured in the littoral and upper part of the pelagic zone. The observed narrow trophic niche of Arctic char, compared with perch and roach, is also a limiting factor for this species (Sandlund et al., ). European whitefish Coregonus lavaretus L .…”
Section: Introductionmentioning
confidence: 99%
“…Sandlund, Haugerud, Rognerud and Borgstrøm (2013) showed that there was a marked segregation in habitat use, with Arctic char observed in the profundal and deep areas of the pelagic zone, and perch and roach captured in the littoral and upper part of the pelagic zone. The observed narrow trophic niche of Arctic char, compared with perch and roach, is also a limiting factor for this species (Sandlund et al, 2013). European whitefish Coregonus lavaretus L. is one of the most widely introduced fish species in northern Europe and although it has the ability to co-exist, the species has partially or completely displaced many native Arctic char populations (Nilsson & Pejler, 1973;Sandlund et al, 2010Sandlund et al, , 2016Svardson, 1976).…”
mentioning
confidence: 99%